Exploring Enabling Factors of E-Recruitment Adoption in the Public Sector and Its Contribution to Public Value Creation - Altino, Iqbal Caraka; Sensuse, Dana Indra; Lusa, Sofian; Putro, Prasetyo Adi Wibowo; Wibowo, Wahyu Setyawan; Cahyaningsih, Elin (Universitas Airlangga, 2025)
Background: E-recruitment systems are increasingly prevalent in the public sector to improve candidate outreach and enhance transparency. Despite their potential, users remain skeptical due to challenges such as recruitment fraud and limited system availability, especially in developing countries like Indonesia. Consequently, it remains unclear how much e-recruitment systems contribute to public value creation. This uncertainty is mainly because there is a lack of research that directly explores the relationship between these systems and public value creation in the public sector, especially in developing countries. Objective: This research aims to examine the factors that influence the use of e-recruitment systems in the public sector and the impact into creation of public values. Methods: This quantitative study collected data from 408 respondents via an online survey, all of whom had used Indonesian National Civil Service Agency's e-recruitment system. Data were analyzed using the Partial Least Square—Structural Equation Model (PLS-SEM) method. Results: The study revealed that system, information, and service quality have a positive impact on perceived usefulness and perceived ease of use and have a positive impact on the use of the e-recruitment system. It also shows that the adoption of an e-recruitment system gives a positive impact on public value creation. Conclusion: This research highlights the critical role of system information quality in fostering e-recruitment adoption and its positive impact on public value creation in the public sector. These findings enrich previous studies that have not yet explored the direct relationship between the use of e-recruitment systems and public value creation. Future research may investigate technological aspects, like artificial intelligence and virtual reality, that could enhance user experience and the adoption of e-recruitment systems in the public sector. Keywords: E-recruitment, PLS-SEM, Information System Success Model, Technology Acceptance Model, Public Value Theory